2002
DOI: 10.1097/00001888-200208000-00009
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Medical Studentsʼ Rotations in Epidemiology and Public Health at State and Local Health Departments

Abstract: Elective rotations in health departments expose medical students to public health practice and career opportunities in applied epidemiology and preventive medicine. State and county epidemiologists and health officers can serve as excellent role models for medical students. In 2000-2001, the authors identified such electives by consulting medical schools' Web sites and by contacting state epidemiologists, teachers of preventive medicine, and medical school associate deans. The authors found that electives were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…There have been many efforts to integrate public health concepts into medical education, in the form of classroom teaching,9–11 field experiences,12–15 dual Doctor of Medicine/Master of Public Health degree programs,1618 and residency rotations 19–21. However, our literature review revealed only two published programs that mention social determinants of health as a thematic focus,19,21 and few undergraduate medical education programs that incorporate teaching about the social determinants of health into their curriculums 2224…”
Section: Introductionmentioning
confidence: 99%
“…There have been many efforts to integrate public health concepts into medical education, in the form of classroom teaching,9–11 field experiences,12–15 dual Doctor of Medicine/Master of Public Health degree programs,1618 and residency rotations 19–21. However, our literature review revealed only two published programs that mention social determinants of health as a thematic focus,19,21 and few undergraduate medical education programs that incorporate teaching about the social determinants of health into their curriculums 2224…”
Section: Introductionmentioning
confidence: 99%
“…A fourth-year public health practice elective could then focus on intermediate level skills and knowledge. 7 The family practice residency curriculum should review and insure the mastery of the basic level and incorporate the intermediate and advanced levels. This could be accomplished by including the content in didactics, insuring that the family practice clinic and faculty model these practices, and by developing an enhanced community medicine experience that includes these topics.…”
Section: Training Methodsmentioning
confidence: 99%
“…Studies reported on a combination of public (n=13) [ 9 , 10 , 16 , 19 , 20 , 25 , 26 , 28 , 32 , 37 , 40 , 42 , 44 ], global (n=9) [ 7 , 14 , 15 , 18 , 24 , 27 , 29 , 31 , 39 ], population (n=9) [ 11 , 13 , 23 , 34 , 38 , 41 , 43 , 45 , 46 ], community (n=6) [ 17 , 21 , 30 , 33 , 35 , 36 ], and epidemiological (n=1) [ 22 ] health interventions. Definitions of each of these were found to be highly overlapping; when reported, objectives of projects, although targeting different “types of public health,” were similar and often included social determinants of health (e.g., poverty, language skills, provider bias, and racism), population-level approaches to medicine, public policy, global burdens of disease, and pandemic preparedness.…”
Section: Reviewmentioning
confidence: 99%
“…The first of these interventions included one-off workshops, simulation exercises, or clerkship electives (50.0%, n=19/38) [ 7 , 10 , 13 - 15 , 17 , 19 , 21 - 23 , 26 , 27 , 29 , 31 , 32 , 37 , 39 - 41 ]. These interventions were often characterized as being stand-alone, time-limited, and isolated in the curriculum, with the rest of the four years being largely unchanged.…”
Section: Reviewmentioning
confidence: 99%